BUSINESS PROCESSES TRANSFORMATION IN THE METHODOLOGY OF MULTILEVEL FINANCIAL MANAGEMENT - Andrey G. Mikheev (Статистика и экономика)
The article discusses the application of process approach to financial management. The multilevel financial management methodology is described. It is based on the delegation of the financial management functions in the downstream division of the organization, process automation, transfer of financial resources between units of different levels of the hierarchical structure of the credit institution, the implementation of a financial management mechanism of the process approach, execution of business processes in the computer environment, using the strategic management of the organization by changing the coefficients, which are the parameters of decentralized control mechanism, using the construction of the «fast» financial indicators, taking into account the terms of financial resources transfer transactions and effective transformation of business processes. The article is focused on the credit institution business management through the application of process transformation to transfer funds business processes.